Molecular typing of Sporothrix schenckii isolates from cats in Malaysia. Issue 4 (27th February 2015) - Kano, Rui; Okubo, Miki; Siew, Han Hock; Kamata, Hiroshi; Hasegawa, Atsuhiko
Summary Epidemiological data on the aetiologic agents of feline sporotrichosis in Malaysia have not been reported, though human sporotrichosis in Malaysia is reported to be transmitted primarily via cat scratch. To the best of our knowledge, the present report is the first study of the molecular epidemiology of Sporothrix schenckii isolates from cats with sporotrichosis in Malaysia. In the present work, we characterised 18 clinical isolates from cats in Malaysia based on molecular properties, including sequence analyses of the calmodulin gene and the rDNA ITS region and selective PCR of mating type (MAT) loci. In this study, isolates from feline sporotrichosis were identified as a S. schenckii sensu stricto by sequence analyses of the calmodulin gene and the internal transcribed spacer (ITS) region. Notably, phylogenetic analysis of the ITS confirmed assignment to clinical clade D (and not C) of S. schenckii sensu stricto. Therefore, clinical clade D of S. schenckii sensu stricto appeared to be the prevailing source of feline sporotrichosis in Malaysia. The ratio of MAT1‐1‐1:MAT1‐2‐1 in these Malaysian isolates was found to be 1 : 0. This result suggested that a clonal strain of S. schenckii is the prevailing causative agent of feline sporotrichosis in Malaysia.